2004
DOI: 10.1007/s00122-003-1571-y
|View full text |Cite
|
Sign up to set email alerts
|

rym15 from the Japanese cultivar Chikurin Ibaraki 1 is a new barley mild mosaic virus (BaMMV) resistance gene mapped on chromosome 6H

Abstract: Breeding for resistant cultivars is the only way to prevent high yield loss in barley caused by the soil-borne barley mild mosaic virus (BaMMV) complex. We have characterized the BaMMV resistance of barley cv. Chikurin Ibaraki 1. Doubled haploid lines were obtained from the F(1) between the susceptible six-rowed winter barley cultivar, Plaisant, and Chikurin Ibaraki 1. Each line was tested for reaction to BaMMV by mechanical inoculation followed by DAS-ELISA. Of 44 microsatellites that covered the genome, 22 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Using DHs, resistance genes rym4 (Graner and Bauer 1993), rym5 (Graner et al 1999), the BaYMV/BaYMV-2 resistance of cv. 'Chikurin Ibaraki 1' (Werner et al 2003a), rym13 (Werner et al 2003b) and rym15 (Le Gouis et al 2004) have been mapped and co-segregating markers have been developed for rym11 using DHs in combination with a recombinant interval mapping approach (Nissan-Azzouz et al 2005). The DH populations facilitated a simultaneous test for BaMMV, BaYMV-1 and BaYMV-2 and showed that rym4 is effective against BaMMV and BaY-MV, and that rym5 and rym11 are effective against all three viruses (Graner et al 1999;Pellio et al 2005;Nissan-Azzouz et al 2005), while in 'Chikurin Ibaraki 1' the BaMMV resistance is inherited independently from the BaYMV/BaY-MV-2 resistance (Werner et al 2003a;Le Gouis et al 2004).…”
Section: Dhs In the Localisation Of Resistance Genes Against The Soilmentioning
confidence: 98%
See 2 more Smart Citations
“…Using DHs, resistance genes rym4 (Graner and Bauer 1993), rym5 (Graner et al 1999), the BaYMV/BaYMV-2 resistance of cv. 'Chikurin Ibaraki 1' (Werner et al 2003a), rym13 (Werner et al 2003b) and rym15 (Le Gouis et al 2004) have been mapped and co-segregating markers have been developed for rym11 using DHs in combination with a recombinant interval mapping approach (Nissan-Azzouz et al 2005). The DH populations facilitated a simultaneous test for BaMMV, BaYMV-1 and BaYMV-2 and showed that rym4 is effective against BaMMV and BaY-MV, and that rym5 and rym11 are effective against all three viruses (Graner et al 1999;Pellio et al 2005;Nissan-Azzouz et al 2005), while in 'Chikurin Ibaraki 1' the BaMMV resistance is inherited independently from the BaYMV/BaY-MV-2 resistance (Werner et al 2003a;Le Gouis et al 2004).…”
Section: Dhs In the Localisation Of Resistance Genes Against The Soilmentioning
confidence: 98%
“…Tuvesson et al 2006). Newly identified genes like rym15 on chromosome 6H (Le Gouis et al 2004) or the BaYMV/BaYMV-2 resistance of 'Chikurin Ibaraki 1' on chromosome 5H (Werner et al 2003) can be incorporated easily in such pyramiding strategies.…”
Section: Dhs In Pyramiding Of Resistance Genes Against the Barley Yelmentioning
confidence: 98%
See 1 more Smart Citation
“…RAPDs, AFLPs, SSRs and STSs, have been developed for resistance genes rym4, rym5, rym9 and rym11 (Bauer et al, 1997;Graner et al, 1999a;Ordon et al, 1999;Pellio et al, 2000Pellio et al, , 2005Werner et al, 2000) and just recently for the BaYMV/BaYMV-2 resistance of 'Chikurin Ibaraki 1' (Werner et al, 2003a) and the BaMMV resistance of this variety (Le Gouis et al, 2004). In addition, respective markers are also available for the BaMMV resistance gene rym13 of the Taiwanese variety 'Taihoku A' (Werner et al, 2003b) as well as for Rym14 Hb and Rym16 Hb derived from Hordeum bulbosum (Ruge et al, 2003(Ruge et al, , 2004.…”
Section: Resistance To the Barley Yellow Mosaic Virus Complexmentioning
confidence: 98%
“…Genetic analyses resulted in the identification of different recessive resistance genes within the primary gene pool of barley (Götz and Friedt, 1993; Ordon and Friedt, 1993; Konishi et al., 1997). Using molecular techniques, these recessive resistance genes were mapped on chromosomes 1H, 3H, 4H, 5H and 6H and PCR‐based markers were developed that are easy to handle (Graner and Bauer, 1993; Ordon et al., 1995; Bauer et al., 1997; Graner et al., 1995, 1996, 1999a,b; Saeki et al, 1999; Werner et al., 2000, 2003a,b;Le Gouis et al., 2004; Nissan‐Azzous et al., 2005; Pellio et al., 2005; for overview cf. Ordon et al., 2005; Friedt and Ordon, 2007; Fig.…”
Section: Sources and Genetics Of Resistance/tolerancementioning
confidence: 99%